Indications and outcomes of paediatric tracheotomy: a descriptive study using a Japanese claims database. Issue 12 (17th December 2019) - Mizuno, Kayoko; Takeuchi, Masato; Kishimoto, Yo; Kawakami, Koji; Omori, Koichi
Abstract : Objective: To examine the incidence of and indications for paediatric tracheotomy to clarify the disease burden relevant to tracheotomy in a population-based context. Design: A descriptive analysis of a retrospective cohort. Setting: This study utilised a nationwide claims database in Japan constructed by JMDC (Tokyo, Japan). The database includes claims data for approximately 3.75 million insured persons (approximately 3.1% of the population of Japan) comprising mainly company employees and their family members. Participants: We identified children registered to have undergone tracheotomy from 2005 to 2017 among about 1.2 million children aged 0–15 years. Main outcome measures: The characteristics of the study population, and indications for tracheotomy, duration of hospital stay, duration of mechanical ventilation, duration of tracheotomy dependence, complications related to tracheotomy and death were assessed. When there were multiple indications, classification for a child into multiple groups was allowed. Results: The study included 215 children (120 males, 56%). The median age at tracheotomy was 0.8 years. The most common age at tracheotomy was less than 12 months (n=127, 59.1%). The most common indications for tracheotomy were chronic lung disease (n=79, 36.7%), followed by neuromuscular disease (n=77, 35.8%), cardiovascular disease (n=53, 24.3%), upper airway obstruction (n=43, 20%), premature birth and related conditions (n=34, 15.8%), trauma (n=16, 7.4%), prolonged ventilation due to other causes (n=12, 5.6%) and malignancy (n=9, 4.2%). The median duration of tracheotomy dependence was 17.2 months. During the follow-up period, decannulation was achieved in 84 children (39.1%), and the median time from tracheotomy to decannulation was 12.0 months. Conclusions: Most paediatric tracheotomies were performed due to chronic underlying diseases, and the mean duration of tracheotomy dependence was nearly 1-½ years. The long-term duration of tracheotomy dependence might have some impacts on patients' physical and mental development and the quality of life.